2018
DOI: 10.3389/fpsyg.2018.00657
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response to Facial Expressions in Peripersonal Space Determines Interpersonal Distance in a Social Interaction Context

Abstract: Accurate control of interpersonal distances in social contexts is an important determinant of effective social interactions. Although comfortable interpersonal distance seems to be dependent on social factors such as the gender, age and activity of the confederates, it also seems to be modulated by the way we represent our peripersonal-action space. To test this hypothesis, the present study investigated the relation between the emotional responses registered through electrodermal activity (EDA) triggered by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 85 publications
10
78
4
Order By: Relevance
“…We do not know if observers perceive avatars -for their artificial nature -to be more or less gender-neutral, but so it seems when inspecting the data from our second experiment. Note that, Iachini et al (2014; found an interaction of subject gender and avatar gender but others did not (Cartaud, Ruggiero, Ott, Iachini, & Coello, 2018;Welsch et al, 2018). Thus, the specific rendering of the avatars in VEs may be crucial.…”
Section: Discussionmentioning
confidence: 91%
“…We do not know if observers perceive avatars -for their artificial nature -to be more or less gender-neutral, but so it seems when inspecting the data from our second experiment. Note that, Iachini et al (2014; found an interaction of subject gender and avatar gender but others did not (Cartaud, Ruggiero, Ott, Iachini, & Coello, 2018;Welsch et al, 2018). Thus, the specific rendering of the avatars in VEs may be crucial.…”
Section: Discussionmentioning
confidence: 91%
“…Perception of peripersonal space was investigated through a widely used reachability judgment task (Grade et al, 2015;Bartolo et al, 2018;Cartaud et al, 2018). However, we slightly modified this perceptive task to match the direction of the force-field perturbation (Coriolis force applied orthogonally to the main direction of movement).…”
Section: Reproduction Of Reachability Judgment Task Featuresmentioning
confidence: 99%
“…The space surrounding individuals is an important area because it is where people interact with social stimuli in the external environment. Social psychology and neurocognitive research has focused on the space around our bodies, indicating that there is a particular relationship between the interpersonal social space (comfort distance) and peripersonal action space (reachability distance) (Iachini et al, 2015;Cartaud et al, 2018;D'Angelo et al, 2019;Spaccasassi et al, 2019). Interpersonal space (IPS) is defined by social psychology as a safety buffer zone that individuals maintain between themselves and others (Hall, 1966;Sommer, 1969;Hayduk, 1983).…”
Section: Introductionmentioning
confidence: 99%